Are Conventional Type 1 Dendritic Cells Critical for Protective Antitumor Immunity and How? - Cancel, Jean-Charles; Crozat, Karine; Dalod, Marc; Mattiuz, Raphaël (Frontiers in Immunology, 2019)
Dendritic cells (DCs) are endowed with a unique potency to prime T cells, as well as to orchestrate their expansion, functional polarization and effector activity in non-lymphoid tissues or in their draining lymph nodes. The concept of harnessing DC immunogenicity to induce protective responses in cancer patients was put forward about 25 years ago and has led to a multitude of DC-based vaccine trials. However, until very recently, objective clinical responses were below expectations. Conventional type 1 DCs (cDC1) excel in the activation of cytotoxic lymphocytes including CD8+ T cells (CTLs), natural killer (NK) cells, and NKT cells, which are all critical effector cell types in antitumor immunity. Efforts to investigate whether cDC1 might orchestrate immune defenses against cancer are ongoing, thanks to the recent blossoming of tools allowing their manipulation in vivo. Here we are reporting on these studies. We discuss the mouse models used to genetically deplete or manipulate cDC1, and their main caveats. We present current knowledge on the role of cDC1 in the spontaneous immune rejection of tumors engrafted in syngeneic mouse recipients, as a surrogate model to cancer immunosurveillance, and how this process is promoted by type I interferon (IFN-I) effects on cDC1. We also discuss cDC1 implication in promoting the protective effects of immunotherapies in mouse preclinical models, especially for adoptive cell transfer (ACT) and immune checkpoint blockers (ICB). We elaborate on how to improve this process by in vivo reprogramming of certain cDC1 functions with off-the-shelf compounds. We also summarize and discuss basic research and clinical data supporting the hypothesis that the protective antitumor functions of cDC1 inferred from mouse preclinical models are conserved in humans. This analysis supports potential applicability to cancer patients of the cDC1-targeting adjuvant immunotherapies showing promising results in mouse models. Nonetheless, further investigations on cDC1 and their implications in anti-cancer mechanisms are needed to determine whether they are the missing key that will ultimately help switching cold tumors into therapeutically responsive hot tumors, and how precisely they mediate their protective effects.